Head and neck dermatitis is exacerbated by Malassezia furfur colonization, skin barrier disruption, and immune dysregulation - Chu, Howard; Kim, Su Min; Zhang, KeLun; Wu, Zhexue; Lee, Hemin; Kim, Ji Hye; Kim, Hye Li; Kim, Yu Ri; Kim, Seo Hyeong; Kim, Wan Jin; Lee, Yang Won; Lee, Kwang Hoon; et al. (Frontiers in Immunology, 2023)
Head and neck dermatitis (HND) is a refractory phenotype of atopic dermatitis (AD) and can be a therapeutic challenge due to lack of responsiveness to conventional treatments. Previous studies have suggested that the microbiome and fungiome may play a role in inducing HND, but the underlying pathogenic mechanisms remain unknown. This study aimed to determine the link between HND and fungiome and to examine the contribution of Malassezia furfur. To identify the effect of the sensitization status of M. furfur on HND, 312 patients diagnosed with AD were enrolled. To elucidate the mechanism underlying the effects of M. furfur, human keratinocytes and dermal endothelial cells were cultured with M. furfur and treated with Th2 cytokines. The downstream effects of various cytokines, including inflammation and angiogenesis, were investigated by real-time quantitative PCR. To identify the association between changes in lipid composition and M. furfur sensitization status, D-squame tape stripping was performed. Lipid composition was evaluated by focusing on ceramide species using liquid chromatography coupled with tandem mass spectrometry. As a result, Increased sensitization to M. furfur was observed in patients with HND. Additionally, sensitization to M. furfur was associated with increased disease severity in these patients. IL-4 treated human keratinocytes cultured with M. furfur produced significantly more VEGF, VEGFR, IL-31, and IL-33. IL-4/M. furfur co-cultured dermal endothelial cells exhibited significantly elevated VEGFR, TGF-β, TNF-α, and IL-1β levels. Stratum corneum lipid analysis revealed decreased levels of esterified omega-hydroxyacyl-sphingosine, indicating skin barrier dysfunction in HND. Finally, M. furfur growth was inhibited by the addition of these ceramides to culture media, while the growth of other microbiota, including Cutibacterium acnes, were not inhibited. Under decreased levels of ceramide in AD patients with HND, M. furfur would proliferate, which may enhance pro-inflammatory cytokine levels, angiogenesis, and tissue remodeling. Thus, it plays a central role in the pathogenesis of HND in AD.